Jean Baudrillard [ fatal theories - Clarke, David B. , 1964- (International library of sociology, 2009)
Jean Baudrillard was one of the most influential, radical, and visionary thinkers. Employing Baudrillard's key concepts, such as simulation, disappearance, and symbolic exchange, and deploying his